2005
DOI: 10.1111/j.1477-9730.2005.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Photogrammetry and 3D laser scanning as spatial data capture techniques for a national craniofacial database

Abstract: Photogrammetry is a non‐contact, high‐accuracy, practical and cost‐effective technique for a large number of medical applications. Lately, three‐dimensional (3D) laser scanning and digital imaging technology have raised the importance of digital photogrammetry technology to a new height in craniofacial mapping. Under the support of the Eighth Malaysian Development Plan, the Ministry of Science, Technology and the Environment (MOSTE) Malaysia allocated a grant to establish procedures for the development of a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Automatic detection is likely to be faster than the use of physical markers, but it necessitates a careful control of experimental conditions; additionally, it may be of difficult application in patients with facial scars or with hairs and nevi. Also, a dark complexion may obtrude the digitization (Majid et al, 2005). The number of markers used in the current investigation is well comparable to those reported in previous studies, that ranged between 15-20 (Coulson et al, 2002;Frey et al, 1999;Giovanoli et al, 2003;Johnston et al, 2003;Tzou et al, 2005) and 30-34 (Nooreyazdan et al, 2004;Trotman et al, 1998b;Weeden et al, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Automatic detection is likely to be faster than the use of physical markers, but it necessitates a careful control of experimental conditions; additionally, it may be of difficult application in patients with facial scars or with hairs and nevi. Also, a dark complexion may obtrude the digitization (Majid et al, 2005). The number of markers used in the current investigation is well comparable to those reported in previous studies, that ranged between 15-20 (Coulson et al, 2002;Frey et al, 1999;Giovanoli et al, 2003;Johnston et al, 2003;Tzou et al, 2005) and 30-34 (Nooreyazdan et al, 2004;Trotman et al, 1998b;Weeden et al, 2001).…”
Section: Discussionsupporting
confidence: 77%
“…Here, we report on an alternative approach using close range laser altimetry, which is capable of sampling at very high resolution (1 mm point interval) and, once calibrated, requires minimal postprocessing. Close range laser scanning has previously been used in a range of applications including medical/ anthropological (Majid et al, 2005) and palaeontological (Bethoux et al, 2004) studies, but 3D analysis applications in fluvial contexts are limited. In their investigations of the interaction of solutes and colloids with a moving sand bed, Packman et al (1997) and Packman and Brooks (2001) demonstrated the potential of using a laser profiler in flume experiments, albeit at relatively low spatial resolution to derive bedform parameters (height, wavelength).…”
Section: Discussion: Case Studymentioning
confidence: 99%
“…This last method is likely to be faster than the use of physical markers, but the actual performance of the automatic tracking should be verified in patients with facial scars, hairs, nevi or with a dark complexion 11 . Also, there should be a facial area to be used as a stable reference for subsequent animations 17,18 .…”
Section: [ ( F I G _ 3 ) T D $ F I G ]mentioning
confidence: 99%